2018
DOI: 10.21595/jve.2017.18968
|View full text |Cite
|
Sign up to set email alerts
|

Removal mechanism of ultrasonic vibration and ELID composite plane grinding based on ultrasonic vibration of nano-ceramic workpiece

Abstract: To realize the high efficiency mirror surface grinding of hard brittle materials (such as nano-ceramic material), this work firstly constructs an experimental platform for workpiece ultrasonic vibration and ELID combined plane grinding according to the processing mechanism of ultrasonic vibration assisted grinding and ELID grinding; then, based on the removal mechanism of hard brittle material, this work analyzes the kinematics of single abrasive grit with workpiece ultrasonic vibration plane grinding, and stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…It was concluded that the MRR increased with an increase of grinding depth at the lower speed of grinding wheel. Shao et al [ 21 ] studied the characteristics of the oxide film in UA-ELID grinding of nanoceramics and analyzed its effect on machining quality and efficiency. Zhao et al [ 22 ] conducted a series of tests and found that during the UA-ELID grinding, the grinding force was reduced by 60%, the MRR increased by 70%, and the surface roughness dropped by 10%, as compared to the respective parameters of the C-ELID grinding.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that the MRR increased with an increase of grinding depth at the lower speed of grinding wheel. Shao et al [ 21 ] studied the characteristics of the oxide film in UA-ELID grinding of nanoceramics and analyzed its effect on machining quality and efficiency. Zhao et al [ 22 ] conducted a series of tests and found that during the UA-ELID grinding, the grinding force was reduced by 60%, the MRR increased by 70%, and the surface roughness dropped by 10%, as compared to the respective parameters of the C-ELID grinding.…”
Section: Introductionmentioning
confidence: 99%
“…The method would improve the finishing effect of the grinding wheel in the realization of online dressing, increase machining efficiency and quality of the grinding wheel, and finally results in an efficient mirror continuous finishing technique. [20][21][22] However, the effect of the additional ultrasonic on the online dressing for grinding wheel has not been fully studied. Therefore, this paper will carry out research in this area, in order to obtain a breakthrough and to promote the further development of the ultrasonic ELID composite grinding technology.…”
Section: Introductionmentioning
confidence: 99%